2022
DOI: 10.21873/invivo.13035
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Prognostic Factors Determining Outcomes of Treatment in Gastric Cancer Surgery

Abstract: Background/Aim: The purpose of this study was to examine the impact of clinicopathological prognostic factors on tumor resectability, perioperative complications, and 5year survival rates in patients with gastric cancer treated surgically. Patients and Methods: A cohort of 834 patients operated on for gastric cancer between 2007 and 2016 was analyzed. Results: Patients over 70 years of age manifested a significantly higher rate of overall complications, systemic complications, surgical complications, periopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…Conversely, other authors have found that elderly patients have a significantly worse prognosis than younger patients [63,64]. Guner et al and Kulig et al suggested that old age is associated with worse DFS and OS in GC patients, respectively [65,66]. These findings are supported by other authors, such as Talebi et al, who identified age >60 years as an independent prognostic factor for worse prognosis in GC [67].…”
Section: Age At Diagnosis and Gc Prognosismentioning
confidence: 74%
“…Conversely, other authors have found that elderly patients have a significantly worse prognosis than younger patients [63,64]. Guner et al and Kulig et al suggested that old age is associated with worse DFS and OS in GC patients, respectively [65,66]. These findings are supported by other authors, such as Talebi et al, who identified age >60 years as an independent prognostic factor for worse prognosis in GC [67].…”
Section: Age At Diagnosis and Gc Prognosismentioning
confidence: 74%